Արդինի–Մուսասիրի տեղորոշման շուրջ - Սարգսյան, Արտակ («Զանգակ - 97»)
The localization of KUR/URUArdini-Musasir is one of the most debatablc points in Urartian studies. Agrceing with the existing opinion expressed in science about Musru - Arinu and Musasir - Ardini, we assume, however, that this country and lown were located in Moukc, which is appropriate to Midgas region ils center. Düring the Urartian period Ardini-Musasir was included in Moukc of the State of Greater Armenia. These approachcs are bascd mainly on the inscriptions of Assyrian king's travellings in the direction of Musru - Arinu and Musasir - Ardini. According to them Musru and Arinu were located between modern Zengan and Alaman to the from Takh, in front of Arnos. Musasir - Ardini was located on the banks of Karkh and Urmia lakes, as well as on the banks of Rshtunik and Khezil, in the territory of Irakion Krdstan and more to the northe, where Ardini - Musasir used to bc located, according to the Assiryan sources, meny other contries and settleinants, and just the neighborhood of Mahkert Tun, probahly beloinged to the generations of Inner Zamwy's monager and was callcd Mekdear - Mahkert Tun.
Keywords: Պատմություն; Տեղագրություն